Study of hematological parameters among blood donors in Duhok city - Sawer Sabri Mizouri (Zanco Journal of Medical Sciences)
Background and objective: Changes in peripheral blood parameters are commonly seen in physiological, stressful and pathological conditions. The aim of this research was to study the abnormalities in hematological parameters of the blood donors in Duhok blood banking center.